Analisis Motif Bantuan Luar Negeri Indonesia Terhadap Krisis di Afghanistan Tahun 2020-2021 - Putri, Anggi Koenjaini; Ramadhanti, Hendrina Nur Alifia; Puspita, Rifki Alif; Yasid, Fadilah; Setyaningtyas, Dwi (Global and Policy Journal of International Relations, 2022)
ABSTRACTThe humanitarian crisis that has occurred in Afghanistan in the last few years, especially in 2020-2021, Indonesia has had a strong historical relationship with Afghanistan since the early days ofindependence. Now through a statement, the Indonesian Minister of Foreign Affairs is committed toproviding assistance and sustainable development for the Afghan people. This study aims to answerthe motives for Indonesia's foreign aid to Afghanistan and how this assistance impacts thedevelopment of Afghan society. The research method used to conduct the analysis is the descriptiveanalysis method with a qualitative approach, using secondary data. In the end, the motive forIndonesia's foreign aid tends to be humanitarian motives, identity, and ideological motives. In thisassistance are a series of forms of construction in establishing strategic relations between Indonesiaand Afghanistan. Indonesia's strategic rationale has a role as a mediator in reconciling the conflictthat occurred in Afghanistan in creating peace. The economic reason supports the interests ofsustainable development in reconstructing the crisis that occurred in Afghanistan by restoringhuman security as a form of solidarity.Keywords: Indonesian Foreign Aid, Afghanistan Humanitarian Crisis, Aid Motives, DevelopmentAssistance.DOI: https://doi.org/10.33005/jgp.v10i01.3574